Heterologous expression, purification, natural abundance 2D NMR assignment and in silico amyloid propensity prediction of the brain natriuretic peptide hormone - Hichri,Elias (2024)
Natriuretic peptides (NPs), such as atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), are hormones produced in the heart’s cardiomyocytes. ANP has been shown to form amyloids, which prevent the heart from functioning properly, ultimately increasing the risk of congestive heart failure (CHF). BNP also has been found in amyloid structures within the heart. Here, multiple algorithms have been used to predict which sequences within BNP and its precursors that are amyloidogenic. A laboratory protocol was established to obtain a pure sample of BNP, where it was heterologously expressed as the fusion protein his6-EDDIE-BNP in BL21(DE3)pLysS E. coli, forming inclusion bodies (IBs). These were obtained through sonication cell lysis, where the IBs were dissolved in a urea solution. BNP was obtained through autoproteolysis, then purified through reverse-phase HPLC and lyophilization. NMR assignments of BNP resonances were performed via natural abundance of 15N and 13C through 1H-1H TOCSY, 1H-1H NOESY, 13C HSQC-TOCSY, 13C HMBC, 15N HSQC and 15N HSQC-TOCSY experiments. The chemical shifts for BNP were used to calculate secondary chemical shifts for C=O, CA, CB, N, HN and HA relative to random coil chemical shifts. The secondary chemical shift analyses showed that BNP is unstructured in solution.
Keywords: brain natriuretic peptide; BNP; NMR; assignment; natural abundance; chemical shift; amyloid propensity; EDDIE; biophysical chemistry; autoproteolysis; inclusion bodies; heterologous expression